EXPRESSÃO DE PRODUÇÃO E QUALIDADE DE GRÃOS EM AVEIA PELO MOMENTO DE APLICAÇÃO DE NITROGÊNIO APÓS EMERGÊNCIA - Silva, Adair J. d.; Krüger, Cleusa A. M. B.; Pinto, Fernando B.; Battisti, Gabriel K.; Silva, José A. G. d.; Gaviraghi, Juliano (Salão do Conhecimento, 2013)
Resumo